Berpikir Kreatif Siswa Dalam Memecahkan Masalah Kontekstual Matematika Ditinjau Dari Tipe Kepribadian - Imil Hidayati; Achmad Dhany Fachrudin; Siti Nuriyatin (LPPM STKIP PGRI Sidoarjo, 2020)
The ability to think creatively is a skill that is really needed by someone in solving problems, but everyone has a different creative way of thinking because everyone has various types of personality. The purpose of this study was to describe the analysis of students' creative thinking in solving contextual mathematics problems in terms of sanguine, choleric, melancholy, and phlegmatic personality types. This research is a descriptive study using a qualitative approach. The research subjects are four students of class VII-3 SMP Negeri 1 Krembung. Each personality type is represented by one subject. The data obtained in this study are personality test results, contextual problem solving test results, and interview data. The data obtained were analyzed by describing the components of creative thinking, namely fluency, flexibility, and novelty. The research results were obtainedphlegmatic and melancholy personality types understand the problem and the information at hand, reveal what is known and asked, and can generate diverse and different ideas. Meanwhile, sanguine and choleric personality types have not been able to generate diverse and different ideas. Phlegmatic and melancholy personality types are able to fulfill fluency, flexibility, and novelty components, sanguinis personality types have not been able to fulfill fluency, flexibility, and novelty components, whereas choleric personality types are only able to fulfill fluency components.